STRUKTUR KOMUNITAS UDANG DI PERAIRAN EKOSISTEM MANGROVE DESA BAGAN ASAHAN KECAMATAN TANJUNGBALAI KABUPATEN ASAHAN PROVINSI SUMATERA UTARA - Nurasiah Riza; Yunasfi Djayus; Ani Suryanti (AQUACOASTMARINE, 2017)
The condition of mangrove in Asahan regency is currently under pressure due to its utilization and less concern management in sustainability aspects. The decrease of mangrove area will have a direct impact for fishery resources especially shrimp. The purpose of this research was to know about community structure of shrimp in Ecosystem mangrove waters of Bagan Asahan Village, Tanjungbalai District, Asahan Regency, North Sumatera Province. This research was conducted for 3 months from March – May 2017. The method of this research used purposive sampling and determined 3 stations sampling that was near tourist and settlement area, estuary and toward beach. There were 8 shrimp found in ecosystem mangrove. Metapenaeus lysianassa had highest abundance of 38%, Penaeus merguiensis 33%, Metapenaeus affinis 16%, Macrobrachium equidens 9%, Leptocarpus potamiscus 1%. Penaeus monodon, Exopalaeomon styliferus and Squilla mantis had lowest abundance with value 0%. The value of Diversity Index (H') of shrimp ranged from 1.027 to 1.447, the value of Evennes Index ranged from (E) 0.741 to 0.964 and the Dominance Index (D) ranged from 0.271 to 0.402.Keyword: Bagan Asahan, Coummunity Structure, Shrimp